Space, Time, Myth, and Morals: A Selection of Jao Tsung-i's Studies on Cosmological Thought in Early China and Beyond - Jao, Tsung-i (Brill, 2022)
The articles assembled in this volume present an important selection of Professor Jao Tsung-i's research in the field of the early Chinese intellectual tradition, especially as it concerns the human condition. Whether his focus is on myth, religion, philosophy or morals, Jao consistently aims to describe how the series of developments broadly associated with the Axial Age unfolded in China. He is particularly interested in showing how early China had developed its own notion of transcendence as well as a system of prediction and morals that enabled man to act autonomously, without recourse to divine providence.